An evolutionary account of the prevalence of personality traits that impair intimate relationships. (May 2016) - Apostolou, Menelaos
Abstract: Personality traits such as low emotional stability and low empathy have a considerable negative impact on an individual's mating success. This impact is more severe in cases where such traits reach extreme levels and are classified as personality disorders. Several evolutionary models have been proposed to account for the relative high prevalence of these apparently maladaptive traits. The present paper contributes to the explanatory power of these models by putting forward the hypothesis that in ancestral human societies selection pressures on personality traits that predict success in intimate relationships had been weak. The reason why is that mate choice had been controlled by parents, mainly fathers, who did not place considerable weight on these traits in a prospective son- and daughter-in-law, and who were willing to impose substantial costs on their children in order to benefit themselves from a marriage alliance. Highlights: An evolutionary explanation of the prevalence of personality traits that impair relationships. An evolutionary explanation of the prevalence of personality disorders Applies the theory of parent–offspring conflict to understand the evolution of personality traits.